Effect of Electrolyte Composition on Structural and Photoelectrochemical Properties of Titanium Dioxide Nanotube Arrays Synthesized by Anodization Technique (Baghdad Science Journal, 2020)
The present work involves studying the effect of electrolyte composition [@1= 0.5 wt.% NH4F / 5% H2O / 5% Glycerol (GLY)/ 90% Ethylene Glycol (EG)] and [ @2= 0.5 wt. % NH4F / 5% H2O / 95% Ethylene Glycol (EG)] on the structural and photoelectrochemical properties of titania nanotubes arrays (TNTAs). TNTAs substrates were successfully carried out via anodization technique and were carried out in 40 V for one hour in different electrolytes (@1, and @2). The properties of physicochemical of TNTAs were distinguished via an X-ray Diffractometer (XRD), Field Emission Scanning Electron Microscope (FESEM), an Energy Dispersive X-ray (EDX), and UV–visible diffuse reflectance. The photoelectrochemical response of TNTAs was evaluated in 0.01M Na2S under the choppy light of a halogen lamp. TNTAs photoelectrode prepared at @1 electrolyte was not sufficient to increase the photocurrent response compared to TNTAs prepared at @2. The TNTAs photoelectrode prepared in the @2 electrolyte confirmed the highest photoconversion efficiency compared to the TNTAs photoelectrode prepared in the @1 electrolyte.